Sub-acute mastitis associated with Methicillin Resistant Staphylococcus aureus in a cow: A case report - Chandrasekaran, Duraisamy; Venkatesan, Periasamy; Tirumurugaan, Krishnasamy Gopalan; Gowri, Balakrishnan; Subapriya, Subramanian; Thirunavukkarasu, Subramanium (Journal of Advanced Veterinary and Animal Research, 2014)
A 5-year old Holstein Friesian cross breed cow was presented to Madras Veterinary College Teaching Hospital with the history of reduced milk yield. Clinical examination of udder revealed normal milk color and soft udder. The milk pH was 7.0, with California Mastitis Test score 3+, Electrical Conductivity 270U, and Somatic Cell Count as 328,000. Isolation and identification of causative agent revealed Methicillin Resistant Staphylococcus aureus (MRSA) from the sub-acute mastitis sample. Agar disc diffusion method for antimicrobial susceptibility revealed that the MRSA was sensitive to Enrofloxacin, Gentamicin, Oxytetracycline and Amoxicillin+Sulbactam. On the other hand, the isolate was resistance to Amoxicillin, Penicillin G, Ceftriaxone and Methicillin. The isolate was positive for ?-lactamase resistance by Nitrocefin test. The MRSA was confirmed for the presence of mecA and blaZ target genes by polymerase chain reaction (PCR). The cow was treated with Enrofloxacin, Vitamin E and inorganic Selenium, and was recovered after 5 days of post-treatment. http://dx.doi.org/10.5455/javar.2014.a35